Analisis Kemampuan Literasi Matematis Mata Kuliah Program Linear di Era Pandemi Covid-19 - Dian Fitri Argarini; Raras Kartika Sari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
This study aims to analyze and describe students' mathematical literacy skills in linear program courses during the covid-19 pandemic. This type of research is a descriptive qualitative research that has been carried out in the Mathematics Education Study Program of IKIP Budi Utomo. The technique of taking research subjects used purposive random sampling method with research instruments in the form of written tests and interview tests. Based on the research data obtained, it was found that the students of the Mathematics Education Study Program of IKIP Budi Utomo had very good mathematical literacy skills. Indicators of mathematical literacy ability, namely formulated, employed, interprete and evaluate are in the very good category